Development of fuzzy controller to control vehicle temperature - Devandran, Krisnan (2012)
Car is the most convenient transportation for each individual compare to public transport. The car which parked at open parking will face problem with increasing temperature inside the car up to 50 degree Celsius. This will make the driver and passenger become uncomfortable while entering the car. Of less significance is damage to temperature sensitive material such as player, GPS system, laptop and LCD screen and plastic components of the car. So the need of temperature controller is really necessary so that the hot air inside the car will be remove and at the same time will reduce the temperature inside the car. This project related to car cooling system and more particularly to a system for cooling passenger compartment of the car without operates the car engine. In this project, a practical application of a closed loop system using fuzzy controller in the vehicle was carried out and control using a Peripheral Integral Controller 16F873A. The temperature data is acquired from SN-LM35DZ temperature sensor and control speed fan to vents hot air out from vehicle powered by solar system in the car. The model has been developed to analysis the system and to get the result of effectiveness of this project.